Implementasi Pembelajaran Inklusif di SD Pelita Bangsa Global Islamic School (GIS) Tangerang Selatan - Itsam Samrotul Fuadah; Esi Hairani (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
In this study the researchers attempted to investigate, find, describe, and explain how SD Pelita Bangsa Global Islamic School (GIS) implements inclusive education learning properly so that the school's existence is still good until now, even more than 2 prospective students with special needs per year who list and want to go to school at the school and the majority of all students with special needs are complete until grade 6. The research uses descriptive research with the data analysis technique model of Miles and Huberman, namely the analysis consists of three flow activities that occur simultaneously, namely: data reduction, data presentation, withdrawal . The results of this study indicate that SD Pelita Bangsa GIS has attempted to plan lessons, especially in Arabic language subjects that are appropriate for students with special needs as described in the General Guidelines for the Implementation of Inclusive Education by the Directorate of PPK-LK Basic Education, Ministry of Education and Culture in 2014 Then, the implementation of inclusive learning, especially in Arabic subjects at SD Pelita Bangsa GIS, has been done well. And lastly, SD Pelita Bangsa GIS has carried out relevant assessments and reports of what schools implementing inclusive programs should do.